The Effect of Product, Word of Mouth, Location, and Price on the Decision to Choose the School of Economics and Business (STIEB) 'Perdana Mandiri' and Its Implications for Student Satisfaction - Lukitaningrum, kristin; Isti Untari, Sri; Rahmawati, Anita; Nurpratiwi, Rahma; Dwi Ariyanti, Tika (International Journal of Management Science and Information Technology, 2024)
The decision to purchase or choose is a process in which consumers make a choice from various alternatives available, selecting the product that best fits their needs. Product quality, including performance, durability, and suitability, plays a significant role in this decision. In the context of higher education, product quality encompasses the study programs offered, innovations, and the added value provided to consumers, in this case, the students. STIEB "Perdana Mandiri" in Purwakarta is one of the most sought-after universities, and this study aims to understand how students make decisions when selecting a campus. This research uses a survey method with Likert scale questionnaires, with a sample of 150 individuals selected through purposive sampling. The method used is descriptive quantitative. The results of the study indicate that the factors of product, word of mouth, location, and price have a positive and significant effect on the decision to choose a campus and also influence student satisfaction. These findings highlight the importance of product quality and external factors in influencing students' decisions when selecting a higher education institution.